Persepsi Pengiklan Terhadap Kebijakan Pemerintah Kota Pangkalpinang pada Penggunaan Baliho PT Cinda Karya Media - Ridwan, Eka Muzalfitri; Sumarno, Sumarno; Hadzami, Meizha; Azzahra, Maharani Fatiya (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
This study examines advertisers' perceptions of Pangkalpinang City's government policy regarding the regulation of billboards and its implications for PT Cinta Karya Media. Billboards are one of the most commonly used outdoor advertising media due to their broad reach and visual impact. However, recent government policies have introduced stricter regulations on the number, location, and duration of billboard installations in order to maintain city aesthetics and order. This research employs a qualitative approach, utilizing in-depth interviews with advertisers operating in Pangkalpinang and management representatives of PT Cinta Karya Media. The findings reveal that many advertisers perceive the policy as restrictive, impacting their advertising strategies and effectiveness. As a result, some have shifted to alternative media, such as digital advertising. PT Cinta Karya Media has responded by adapting its business strategies, exploring new advertising media, and optimizing permissible billboard locations. This study concludes that while the policy contributes positively to urban order, it presents economic challenges, particularly for small and medium advertisers. It recommends that local governments adopt more flexible policies that strike a balance between city planning and business growth. Furthermore, innovation in advertising media is encouraged for both advertisers and media companies.